RADION PRODUCTION IN THE HIGH ENERGY GAMMA-ELECTRON COLLIDERS - Tham, Tran Dinh; Thao, Nguyen Huy; Soa, Dang Van; Thuy, Dao Le; Giang, Bui Thi Ha (Communications in Physics, 2012)
We analyze the potential of Compact Linear Colliders (CLIC) based on the gamma - electron collisions to search for the radion in the Randall - Sundrum (RS) model, where compactification radius of the extra dimension is stabilized by the radion, which is a scalar field lighter than the graviton Kaluza-Klein states. The production of radion in the high energy gamma - electron colliders are calculated in detail. Numerical evaluation shows that if the radion mass is not too heavy then the reaction can give observable cross section in future colliders.